Evolution of Acinetobacter baumannii In Vivo: International Clone II, More Resistance to Ceftazidime, Mutation in ptk - Hua, Xiaoting; Zhou, Zhihui; Yang, Qing; Shi, Qiucheng; Xu, Qingye; Wang, Jianfeng; Shi, Keren; Zhao, Feng; Sun, Long; Ruan, Zhi; Jiang, Yan; Yu, Yunsong (Frontiers in Microbiology, 2017)
Acinetobacter baumannii is an important nosocomial pathogen worldwide. A more comprehensive understanding of the within-host genomic evolution of A. baumannii would provide a molecule basis for improving treatment of A. baumannii infection. To understand the evolutionary mechanism facilitating A. baumannii survived in human body, we here report the genomic analysis of A. baumannii isolated sampled from Chinese patients. We used whole-genome sequencing of A. baumannii isolates from the same patient to determine single-nucleotide variants, insertion sequence mapping, and gene change. The MICs for ten antimicrobial agents were determined. Motility assay and microscopy were performed on the isolated pairs harboring ptk mutations. The gene ptk encoded a putative protein tyrosine kinase involved in the production of capsular polysaccharide. Approximately half (39/86) of the strains isolated from the same patient harbored the same MLST patterns, and during the replacement of international clonal lineage II (ICL-II) and non-ICL-II strains, most of the alteration was that non-ICL-II strain was replaced by ICL-II strain (10/12). A. baumannii was resistant to major antimicrobial agents, whereas the strains were more resistant to ceftazidime (CAZ), azithromycin (AZM) and sulfonamides (S) after within-host evolution. Isolates from the ICL-II lineage displayed greater resistance to antimicrobial agents than did non-ICL-II isolates. Isolates from ICL-II harbored more resistance genes and mobile elements than did non-ICL-II strains. Several lineages evolved a more mucoid phenotype. Genome sequencing revealed that the phenotype was achieved by genetic changes in the ptk gene. ICL-II (especially ST195 and ST208) was the terminal destination for bacteria after within-host evolution. These results indicate that the molecular basis and the treatment for ICL-II strains needed further investigation.